CT-Derived Fractional Flow Reserve (FFRCT): From Gatekeeping to Roadmapping. Issue 2 (May 2020) - Huang, Alex L.; Maggiore, Paul L.; Brown, Richard A.; Turaga, Mansi; Reid, Anna B.; Merkur, Jacob; Blanke, Philipp; Leipsic, Jonathon A.
Coronary computed tomography angiography (CCTA) has emerged as the preferred modality in the diagnosis of coronary artery disease, but it is limited by modest specificity. By applying principles of computational fluid dynamics, flow fraction reserve, a measure of lesion-specific ischemia that is used to guide revascularization, can be noninvasively derived from CCTA, the so-called computed tomography–derived flow fractional reserve (FFRCT ). The accuracy of FFRCT in discriminating ischemia has been extensively validated, and it has been shown to improve the specificity of CCTA. Compared to other stress myocardial perfusion imaging, FFRCT has superior or comparable accuracy. Clinical studies have provided strong evidence that FFRCT has significant prognostic implications and informs clinical decisions for revascularization, serving as a gatekeeper to invasive coronary angiography. In addition, FFRCT-based tools can be used to simulate the physiological consequences of different revascularization strategies, thus providing the roadmap to achieve complete revascularization. Although challenges remain, ongoing research and randomized controlled trials are expected to address current limitations and better define its role in clinical practice.